The Role of Invariant NKT in Autoimmune Liver Disease: Can Vitamin D Act as an Immunomodulator? - Daniel S. Smyk; Athanasios Mavropoulos; Giorgina Mieli-Vergani; Diego Vergani; Marco Lenzi; Dimitrios P. Bogdanos (Canadian Journal of Gastroenterology and Hepatology)
Natural killer T (NKT) cells are a distinct lineage of T cells which express both the T cell receptor (TCR) and natural killer (NK) cell markers. Invariant NKT (iNKT) cells bear an invariant TCR and recognize a small variety of glycolipid antigens presented by CD1d (nonclassical MHC-I). CD1d-restricted iNKT cells are regulators of immune responses and produce cytokines that may be proinflammatory (such as interferon-gamma (IFN-γ)) or anti-inflammatory (such as IL-4). iNKT cells also appear to play a role in B cell regulation and antibody production. Alpha-galactosylceramide (α-GalCer), a derivative of the marine sponge, is a potent stimulator of iNKT cells and has been proposed as a therapeutic iNKT cell activator. Invariant NKT cells have been implicated in the development and perpetuation of several autoimmune diseases such as multiple sclerosis and systemic lupus erythematosus (SLE). Animal models of SLE have shown abnormalities in iNKT cells numbers and function, and an inverse correlation between the frequency of NKT cells and IgG levels has also been observed. The role of iNKT cells in autoimmune liver disease (AiLD) has not been extensively studied. This review discusses the current data with regard to iNKT cells function in AiLD, in addition to providing an overview of iNKT cells function in other autoimmune conditions and animal models. We also discuss data regarding the immunomodulatory effects of vitamin D on iNKT cells, which may serve as a potential therapeutic target, given that deficiencies in vitamin D have been reported in various autoimmune disorders.